Analysis features parameters of polarization ortogonal antennae for MIMO system - Мартынчук, А. А.; Абдуллах Икрам Кадир (ХНУРЭ, 2011)
In this article was derived method of finding the field components of the antenna signal and background noise, or processing in antenna with full polarization receiver. This will result to increase of bit rate of MIMO system on the basis of the use of polarization properties of signals, in the case of a real product. MIMO technology with orthogonal polarizing channels additional provides increase signal to noise ratio and therefore increase in bit rate in wireless.
Keywords: Wi-Fi system; MIMO technology